Measurement of Land Valuation Value and Survival Strategy of Farmers in Rural–Urban Areas - Ahmad Imron Rozuli; Anik Susanti; Dano Purba; Adhinugraha Wirayudha Kusuma; Ryan Renwarin (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. Kedungrejo as a village located on the border of a city village, certainly has consequences for changes in the structure and local institutions of farmers. As a consequence, changes in land spatial planning and livelihoods will dominate, many industrializations, developer housing development, and land use change. The impact that occurs is the crisis of farmer youth, often crop failures due to the market, so that farmers will adapt according to the existing dynamics. This is what is of interest to researchers to analyze the value of the valuation of rural land spatial planning and farmers' survival strategies due to urban attractiveness. With ethno-ecological methods, this research will focus on land value, land benefits, and farmers' survival strategies. Based on the results of the study, it shows that the valuation value of agricultural commodities depends on the type of crops they grow. Namely spinach, kale, kenikir and basil. Each commodity has a different valuation value because it is in accordance with market opportunities, operational costs, and the area of farmers' land. Therefore, the form of active strategies for farmers is in the form of reducing seed operational costs and switching chemical fertilizers to natural fertilizers. Then consider the planting and harvesting time, as well as read market opportunities. The passive strategy of farmers tends to borrow money from middlemen and financial institutions, and reduces the role of workers in the planting phase. Meanwhile, another strategy is to take advantage of social ties between farmers, in the form of mutual cooperation, joint gathering, and maintaining farmer group activities in terms of assistance information, sharing, and water irrigation management.  Keywords: Valuation of Vegetable Farmers, Peripheral Areas, Active Strategies, Passive Strategies and Network Strategies.  Abstrak. Kedungrejo sebagai desa yang terletak di perbatasan desa-kota, tentu mempunyai konsekuensi terhadap perubahan struktur dan pranata lokal petani. Sebagai konsekuensinya perubahan tata ruang lahan dan mata pencaharian akan mendominasi, banyak industrialisasi, pembangunan perumahan developer, dan alih fungsi lahan. Dampak yang terjadi ialah krisis pemuda tani, sering terjadi gagal panen akibat pasar, sehingga dengan kondisi tersebut petani akan beradaptasi sesuai dengan dinamika yang ada. Inilah yang menjadi ketertarikan peneliti untuk menganalisis nilai valuasi tata ruang lahan pedesaan dan strategi bertahan hidup petani yang disebabkan daya tarik perkotaan. Dengan berbekal metode etno-ekologi penelitian ini akan berfokus pada nilai lahan, manfaat lahan, dan strategi bertahan hidup petani. Berdasarkan pada hasil penelitian menunjukkan bahwa nilai valuasi komoditas tani bergantung pada jenis tanaman yang mereka tekuni. Yakni bayam, kangkung, kenikir dan kemangi. Masing masing komoditas mempunyai nilai valuasi berbeda karena sesuai dengan peluang pasar, biaya operasional, serta luas lahan petani. Oleh karena itu, bentuk strategi aktif petani berupa pengurangan biaya operasional bibit dan peralihan pupuk kimia menjadi pupuk alami. Kemudian mempertimbangkan masa waktu tanam dan panen, serta membaca peluang pasar. Strategi pasif petani cenderung meminjam uang kepada tengkulak dan lembaga keuangan, dan mengurangi peran kerja buruh pada fase tanam. Sedangkan strategi lainnya adalah dengan memanfaatkan ikatan sosial antar petani, berupa gotong-royong, rembuk bersama, dan menjaga kegiatan kelompok tani dalam hal informasi bantuan, sharing, serta pengelolaan irigasi air.  Kata Kunci: Valuasi petani sayur, kawasan periferi, strategi aktif, strategi pasif dan strategi jaringan